The Inﬂuences of an Invasive Plant Species (Leucaena leucocephala) on Tree Regeneration in Khao Phuluang Forest, Northeastern Thailand - Marod , Dokrak; Duengkae, Prateep; Kutintara, Utis; Sungkaew, Sarawood; Wachrinrat , Chongrak; Asanok, Lamthai; Klomwattanakul, Narongchai (Agriculture and Natural Resources, 2012)
The inﬂuence of Leucaena (Leucaena leucocephala) on tree regeneration was studied in a natural forest in the Khao Phuluang Ecotourism Development Project, northeastern Thailand. In total, three belt transects of 10 × 150 m were established perpendicular to the edge of the remnant forest (RF) and Leucaena plantation (LP) to study the changes in vegetation structure and species composition along a gradient from the RF into the adjacent LP. The vegetation transect census recorded the living numbers of seedlings, saplings and trees, excluding lianas, and the stem diameter and height were measured for saplings and trees. Light and soil conditions were also investigated. The results showed that the species composition in the LP was very low and only 16 species of 16 genera in 11 families were found. Leucaena had a high stem density and basal area cover of 1,196.7 stems.ha-1 and 13.92 m2.ha-1, respectively. The high density created a closed canopy which reduced the relative light intensity measured as mean ± SD on the ﬂ oor (18.5 ± 5.5%) which was similar to that of the RF (15.56 ± 2.8%). The distribution of the diameter at breast height of Leucaena ﬁ tted a negative exponential growth curve function (r2 = 0.94), indicating the species had successful natural regeneration which was not only from seedlings but also from coppiced stems. The natural regeneration of native species from the RF towards the LP was highly signiﬁ cantly (ANOVA, P < 0.001) different for both the stem density and species number. The stem densities of trees, saplings and seedlings of native species were greater in the RF than in the LP. In addition, not only the native climax species but also pioneer species had less success in establishment in the LP. This would suggest that Leucaena plays an important role in restricting natural forest regeneration by its invasive growing habit which reduces light transmittance to the forest ﬂ oor.